SPECIFIC VELOCITY STRUCTURE OF THE UPPER MANTLE IN THE TRANSBAIKALIA SEGMENT OF THE MONGOLIA-OKHOTSK OROGENIC BELT - V. M. Soloviev; V. V. Chechelnitsky; A. S. Salnikov; V. S. Seleznev; A. V. Liseikin; N. A. Galyova (Геодинамика и тектонофизика, 2017)
The paper presents the results of deep seismic studies on Geophysical Reference Profile 1-SB (Sredneargunsk – Ust-Karenga – Taksimo – Vitim) in East Transbaikalia,Russia. The1200 kmlong profile crosses the major tectonic structures of the Central Asian fold belt: the Argun median massif, the Selenga-Stanovoy and Transbaikalia folded regions, and the Baikal rift zone. Its northwestern fragment extends into the Angara-Lena monocline of the Siberian platform. The southeastern (Transbaikalia) and northwestern (Baikal-Patom) fragments of the profile are based on the spot (differential) seismic sounding technique using explosions and 40-tonne vibrators. The southeastern (Transbaikalia) fragment shows small crustal thickness values (~40 km), an almost horizontal position of the Moho, and high velocities of longitudinal waves (~8.4 km/sec) beneath the Moho. The analysis of parallelism graphs and the dynamic expression of the wave refracted from the Moho suggests a less than 5–10 km thick layer of high velocities and low gradients below Moho. The database on theterritoryofTransbaikaliaincludes ~200 wave arrival times from large earthquakes, which were refracted at the Moho at distances of ~200–1400 km. As part of the tomographic interpretation, using additional DSS data on the Moho, theterritoryofTransbaikaliahas been mapped to show the patterns of the threshold velocity values at the Moho. The seismic data was used to contour an area with high velocity values in the mantle in the central part of the Mongolia-Okhotsk orogenic belt and the neighboring fold structures of Transbaikalia. According to the analysis of the seismic and geologic data on the study area, the mantle layer with high velocity values in the Mongolian-Okhotsk orogenic belt may be represented by the eclogitic rock plates.